Current and future use of dipyridamole in patients with COVID-19 - I. S. Burashnikova; V. M. Tsvetov; K. B. Mirzaev; D. A. Sychev (Izdatelstvo OKI, 2020)
Current use of dipyridamole in COVID-19 is mainly based on its antithrombotic activity, since there is no robust clinical effectiveness data. The decision to use dipyridamole in COVID-19 should be individualized, considering the experimental nature of this treatment.